2011
DOI: 10.2166/wh.2010.169
|View full text |Cite
|
Sign up to set email alerts
|

PCR assay targeting virulence genes of Helicobacter pylori isolated from drinking water and clinical samples in Lahore metropolitan, Pakistan

Abstract: Helicobacter pylorus is considered for chronic gastritis, gastric ulcers and adenocarcinoma and its high infection rate is observed in overcrowded and lower socioeconomic groups in developing countries. This study was designed to identify the role of drinking water in the transmission and prevalence of H. pylori (HP). Selective HP medium was developed for enrichment and presumptive identification of H. pylori by urease, catalase and species specific 16S rRNA tests. The virulence genes (vacA 's' and 'm' regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Roles of contaminated water and even drinking water in transmission of H. pylori have been confirmed previously [17][18][19][20]. Probably, the water sources used for production, washing and processing of these foods samples were contaminated.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Roles of contaminated water and even drinking water in transmission of H. pylori have been confirmed previously [17][18][19][20]. Probably, the water sources used for production, washing and processing of these foods samples were contaminated.…”
Section: Discussionmentioning
confidence: 59%
“…High amount of Aw in meat base food samples, optimum pH and salt levels, presence of appropriate levels of amino acids including arginine, histidine, isoleucine, leucine, methionine, phenylalanine, alanine, valine, proline, serine, and tryptophan favors the for growth of H. pylori [12], this is in addition to unsanitary conditions in their preparation and cross contamination of these foods due to handling by factory and food units staffs. High prevalence of H. pylori in foods with animal origin has been reported previously [5,9,15,17,18,20].…”
Section: Discussionmentioning
confidence: 63%
“…The presence of H. pylori was observed in 4% of the treated water samples from Karachi. A recent study reports the presence of H. pylori in 40% of water samples collected from Lahore, a city located in a different province of Pakistan [16]. The sharp contrast in the positivity rates of these two cities is surprising and raises serious concerns about the quality of water and the water distribution system.…”
Section: Resultsmentioning
confidence: 99%
“…Fujimura et al [45] demonstrated that river water in the natural environment could be a risk factor for H. pylori transmission. H. pylori has previously been detected in drinking water [46, 47]. The presence of H. pylori in water supplies might be the result of contamination from human sewage [4851].…”
Section: Discussionmentioning
confidence: 99%